Performance of State Civil Services as the Impact of Android-Based Attentions Determined by Discipline (Studies at the Palopo State Islamic Institute) - Hamka Hamka; Muhammad Aqsa (Institute of Computer Science (IOCS), 2022)
This study examines the effect of work discipline on employee performance through android based attendance at the State Islamic Institute (IAIN) Palopo City. Path analysis method used in this study with a total sample of 108 people. The results showed that work discipline had no significant effect on performance through android-based absenteeism as a mediating variable